Developing West Java Local History Materials in Sosial Studies Learning - Murdiyah Winarti; Yani Kusmarni; Ayi Budi Santosa; Wildan Insan Fauzi (Social Studies Conference Proceedings, 2022)
Social studies learning based on the local history of West Java aims to build a connection between students and everyday life. Local history materials will familiarize students with the community and living environment well; Have a positive sense of community and place of residence; Know and determine existing values ​​such as hard work, mutual respect, respect, loyal friends, and cooperation/cooperation. The main limitation of this research problem is how to develop West Java Local History material in social studies learning. The historical method explores and describes local West Java historical materials that can be used in social studies learning through heuristics, source criticism, interpretation, and historiography. Aspects of West Java's local history material that can be developed include: the value of local wisdom, local communities and traditional villages in West Java, the history of Sundanese ethnicity, the history of the Cirebon Sultanate, the development of Islamic boarding schools in West Java, Preanger Stelsel, local resistance to western colonial rule, West Java figures, Priangan reorganization, growth of cities in West Java, Pasundan Association, Sekar Rukun, and West Java Governor.